(untitled) (Research, Society and Development, 2020)
Objective: To analyze the epidemiological profile, through associated factors, as well as to determine the coinfection of Tuberculosis with HIV, the analysis of the age group and main regions that have the highest Tuberculosis index in the state of Piaui in the years 2014 to 2019 Methods: This study is a quantitative and retrospective exploratory research from the point of view of the method, and transversal, with regard to the time of study follow-up, through searches in the secondary database, regarding the epidemiology of tuberculosis in the state of Piaui and data collection was done through the Information System for Notifiable Diseases and the Department of Informatics of the Unified Health System. Results: In reference to the results, it was possible to verify that in the years 2014 to 2019 tuberculosis cases were recorded in Piaui, in the Entre Rios region, it stood out for having 2,637 cases in the years surveyed, the highest frequency in relation to the age group was 20 to 39 years old and it was found that co-infection in greater numbers with HIV were negative. These data point to the importance of preventive measures and health promotion, plans to combat suicide and demonstrate the need for a greater focus on tuberculosis. Conclusion: The number of reported cases shows the importance of studying the epidemiological profile of tuberculosis in Piaui with the main objective of reducing the sources of infection, thus identifying the cases through this study.